Analisis Kesalahan Berbahasa Mahasiswa: Kajian Psikolinguistik Terhadap Pembelajar Bahasa Kedua (L2) - Hodijah Batubara; Muhammad Hasyimsyah Batubara (Yayasan Al-Afif, 2025)
This study investigates language errors made by university students in learning English as a second language (L2) from a psycholinguistic perspective. It examines how mental processes such as attention, perception, memory, and speech production influence the emergence of errors in students’ written and spoken English. Using a descriptive qualitative method, the research analyzes essays and oral performance of third-semester English students at STAIN Mandailing Natal. Thefindings indicate that interlingual interference, intralingual overgeneralization, and limited control of linguistic systems significantly contribute to student errors. Psycholinguistically, these errors are rooted in constraints of working memory, cross-linguistic influence, and disruptions in the formulation stage of speech production. The study concludes that language errors should be viewed as indicators of interlanguage development rather than mere deficiencies.